Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah pada PT. BCA Finance Cabang Bukit Tinggi - Dasep Suryanto (COSTING : Journal of Economic, Business and Accounting, 2019)
Banking business is a service business that is based on the principle of trust so that the quality of service issues is a very decisive factor in the success of businesses managed by the company. The purpose of this study was to determine the effect of service quality on customer satisfaction at PT. BCA Finance Bukittinggi Branch. The sample was taken by researchers as many as 150 respondents who were customers of PT. BCA Finance Bukittinggi Branch, the analysis technique used in the study used Regression analysis. The results of this study indicate that: 1) Service Quality with dimensions of Physical Evidence, Reliability, Responsive Capability, Assurance and Empathy has a positive and significant influence on customer satisfaction. From the results of this study, it was suggested to the management of PT. BCA Finance Bukittinggi Branch to conduct periodic evaluations and research to improve service quality, especially in terms of Physical Evidence and Responsiveness to provide training in direct contact with customers, so as to minimize customer complaints and increase customer satisfaction. Keywords: Service Quality, Customer Satisfaction